2020
DOI: 10.3390/separations7010017
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenated High Performance Liquid Chromatography–Tandem Mass Spectrometry Techniques for the Determination of Perfluorinated Alkylated Substances in Lombardia Region in Italy, Profile Levels and Assessment: One Year of Monitoring Activities During 2018

Abstract: In this research paper, we report a hyphenated technique based on ultra-high performance liquid chromatography–tandem mass spectrometry for the determination of twelve Perfluorinated Alkylated Substances in surface and groundwater samples from Lombardia Region during the monitoring activities in 2018 as new emerging and toxic pollutants. A green analytic method, developed by using an online Solid Phase Extraction coupled with UHPLC-MS/MS and previously validated, was applied for 4992 determinations conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
0
5
1
Order By: Relevance
“…Also in this case, the concentrations detected are much higher than those measured in this work. More recently,Barreca et al (2020) reported PFOS concentrations between < LOQ and 29.4 ng L − 1 in 57 river water samples collected in northern Italy, values 13 times higher than those reported in this study (Table4) Llorens et al (2020).…”
contrasting
confidence: 56%
“…Also in this case, the concentrations detected are much higher than those measured in this work. More recently,Barreca et al (2020) reported PFOS concentrations between < LOQ and 29.4 ng L − 1 in 57 river water samples collected in northern Italy, values 13 times higher than those reported in this study (Table4) Llorens et al (2020).…”
contrasting
confidence: 56%
“…Consequently, the mean S/N ratio was calculated with six replicates in every sample analysis and determined by the established GC-MS/MS method. Additionally, the LOQ could be confirmed in the method when the recovery was above 70% and the accuracy was less than 20% [19][20][21].…”
Section: Lod and Loqmentioning
confidence: 99%
“…Because of these strong properties, PFAS are classified as highly persistent pollutants [ 17 ]. Moreover, their resistance to chemical, biological, and physical factors suggests that the human impact on exposure from materials and consumer products is generally lower than that from drinking water and/or contaminated food, such as fish [ 18 , 19 , 20 , 21 , 22 ]. PFAS can accumulate in the human body and, as reported in the literature, their levels decrease slowly over time [ 23 ].…”
Section: Introductionmentioning
confidence: 99%